Creación de un front end usando HTML5, para explotar las funcionalidades de la plataforma Moodle, además de una aplicación móvil android para el manejo oportuno de notificaciones con sincronización a Google Calendar - Parreño Cárdenas, Tatiana Maribel (2016)
This project is to show the usability functionality within a virtual environment, with the potential of HTML5 in the Front End, which combined with e-learning platform Moodle, its functionality was exploited. This requires a satellite application was developed with HTML5, using the web services provided by the Moodle platform. Moodle e-learning platform has its own methodology of virtual learning, for this project and to exploit the features of it, a methodology to measure the project was created to provide a much friendlier and colorful user interface. A methodology for e-learning was analyzed to determine the resources to be used, as necessary and useful for student motivation against this type of environment. In addition it has created a mobile application to facilitate the review of activities without the need to enter the virtual classroom.